In situ Investigation of the Growth of a Tribofilm Consisting of NaYF4 Fluorescent Nanoparticles. Issue 3 (4th May 2018) - Dai, Wei; Chen, Yunyun; Lee, Kyungjun; Sinyukov, Alexander M.; Alkahtani, Masfer; Hemmer, Philip R.; Liang, Hong
ABSTRACT: Tribofilms play a vital role in protecting lubricated surfaces in mechanical systems in motion. To date, understanding tribofilms has been mostly based on ex situ analysis. This research investigates the kinetics of a tribofilm formed on a pair of bearing steels (E52100). Strategically selected illuminative nanoparticles of NaYF4 were added to a base oil in order to enable their tracking. Electrical conductivity was monitored during sliding that was found to be linked to the state of the interface and the tribofilm. Further characterization identified tribochemical reaction products of Y2 O3 that exhibited superior tribological performance. In comparison with mineral oil as the base lubricant, the addition of NaYF4 resulted in a reduction in wear of 82%. This work discovered three stages in tribofilm formation: running in, reactive, and growth. Interestingly, the formation of a tribofilm was dominated more by frictional force than applied load. This is significant because we can now use alternative strategies to generate quality tribofilms.